Analisis Hubungan Pengetahuan Lingkungan Terhadap Keinginan Melakukan Pembelian Produk Organik di Kalangan Mahasiswa di Pekanbaru - Siregar, Dede Iskandar; Binangkit, Intan Diane (Faculty of Economics and Business Universitas Muhammadiyah Riau, 2019)
The previous study explores the relationship of consumer environmental knowledge and purchasing intention on the organic product however conducted without specifying the product. The present study aims to analyze the relationship of environmental knowledge, subjective and objective, on organic product purchasing among university students in Pekanbaru. To this, this study utilizes a positivism paradigma based on survey and literature review. The article used a qualitative data collection method through questionnaires from 124 respondents. Bay using a regression approach, the study confirmed that both subjective and objective knowledge positively related to organic purchasing intention.